DETERMINANTS OF THERAPEUTIC INJECTION OVERUSE AMONG COMMUNITIES IN SINDH, PAKISTAN - Altaf, Arshad; Fatmi, Zafar; Ajmal, Agha; Hussain, Tanweer; Qahir, Henna; Agboatwalla, Mubina (Journal of Ayub Medical College Abbottabad, 2004)
Background: Unsafe injections including reuse of disposable syringe is very common in developing countries including Pakistan. Healthcare providers unnecessarily prescribe injections to patients suggesting that patients ask for injections. We conducted this qualitative study to determine the reasons of overuse of therapeutic injections by the communities in Sindh province of Pakistan. Methods: Using field-tested focus group guides of World Health Organization, eighteen focus group discussions (FGDs) were conducted with community members of rural Sindh, peri-urban and urban Karachi during January-February 2001. Results: Injections are overused in Sindh, Pakistan, because patients prefer them, believing that they provide quick relief, and perceive them as a therapeutic norm and standard practice. According to community members initiative of prescription of injections are taken by doctors. Overuse of injections is of particular concern as patients are not aware of the risks associated with reuse of injection equipment. Doctors and television are considered as the most credible source of providing healthcare information. Conclusion: There is a need to educate communities regarding rationale use of therapeutic injections. Open discussion and frequent communication between doctors and patient should be encouraged. Mass media could play a vital role in educating communities about risks of unsafe injections. Key words: Overuse, unsafe injections, focus groups, patient's awareness, hepatitis B, hepatitis C